2022
DOI: 10.23887/jppsh.v6i2.50139
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Students' Self-Efficacy as the Key to Successful Distance Learning: According to Previous Studies

Abstract: Self-efficacy may be more challenging to achieve in the context of distance learning when students rely on their teachers as their learning source. This study aims to analyze the importance of students' self-efficacy in their distance learning success. This study adapting library research model into the qualitative design, the present study used experts' opinions and previous studies as data sources to answer how students' self-efficacy affects their success in distance learning. Data sources were selected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Thirty articles revealed that online learning could provide opportunities to connect learning with abundant learning sources. Learners can find abundant learning sources independently by utilizing online platforms and fun online learning apps (Al Ghazali, 2020;Cahyani et al, 2021;Dantes, Suryandani et al, 2022). They could use various online platforms beyond the classroom for autonomous learning (Dincer, 2020;Hazaymeh, 2021;Saputra et al, 2021;Putra, 2021;Rahmayanti et al, 2021).…”
Section: Figure 2 Benefits Of Online Learningmentioning
confidence: 99%
“…Thirty articles revealed that online learning could provide opportunities to connect learning with abundant learning sources. Learners can find abundant learning sources independently by utilizing online platforms and fun online learning apps (Al Ghazali, 2020;Cahyani et al, 2021;Dantes, Suryandani et al, 2022). They could use various online platforms beyond the classroom for autonomous learning (Dincer, 2020;Hazaymeh, 2021;Saputra et al, 2021;Putra, 2021;Rahmayanti et al, 2021).…”
Section: Figure 2 Benefits Of Online Learningmentioning
confidence: 99%